2019
DOI: 10.1016/j.omtm.2019.08.011
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Same-Eye Subretinal Sequential Readministration of AAV2-hRPE65v2 in Non-human Primates

Abstract: We have demonstrated safe and effective subretinal readministration of recombinant adeno-associated virus serotype (rAAV) to the contralateral eye in large animals and humans even in the setting of preexisting neutralizing antibodies (NAbs). Readministration of AAV to the same retina may be desirable in order to treat additional areas of the retina not targeted initially or to boost transgene expression levels at a later time point. To better understand the immune and structural consequences of subretinal rAAV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 54 publications
1
15
0
Order By: Relevance
“…Likely facilitated by the immune privilege of the eye, vector administration to one eye could be later on followed by contralateral gene transfer to the second eye, and repeat administration to the same eye is also possible. 37 , 38 Other routes of in vivo vector administration are more typically associated with formation of NABs that prevent re-administration of vector. Furthermore, humans develop NABs to various serotypes during childhood.…”
Section: Main Textmentioning
confidence: 99%
“…Likely facilitated by the immune privilege of the eye, vector administration to one eye could be later on followed by contralateral gene transfer to the second eye, and repeat administration to the same eye is also possible. 37 , 38 Other routes of in vivo vector administration are more typically associated with formation of NABs that prevent re-administration of vector. Furthermore, humans develop NABs to various serotypes during childhood.…”
Section: Main Textmentioning
confidence: 99%
“…Altogether, our results provide safety information at the cellular level for both the surgical technique and the AAV2-hCHM study agent confirming histologic/cellular-level safety signals that up to now were only available through histopathologic studies in normal non-human primates. [48][49][50][51][52] The subretinal injection however, is not without risk. Foveal thinning and the occurrence of full thickness loss of retinal tissue (macular holes) are known complications of the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, transient antibody response against the capsid and cellular immune responses were also noted [reviewed in (30,76,213)]. The low to mild and transient immune responses allowed repeated administration of AAV vectors, either contralateral or in one eye (214,215) or the delivery of two boluses in the same eye (216). Finally, long-term expression could be achieved in most clinical trials, with a decline observed in some after a few years (202,210) [reviewed in (30,76,213)].…”
Section: Eyementioning
confidence: 99%